Assessing the Emotional Intelligence of Gifted and Talented Adolescent Students in the Kingdom of Bahrain. Issue 2 (3rd April 2017) - Al-Hamdan, Najat Sulaiman; Al-Jasim, Fatima Ahmed; Abdulla, Ahmed M.
Abstract : This study assessed the differences in the emotional intelligence of gifted adolescent students and talented adolescent students in Bahrain. The sample consisted of 80 gifted adolescent students and 80 talented adolescent students in Grades 9 through 12. A multivariate analysis of variance (MANOVA) indicates that there were significant differences in emotional intelligence levels, as measured by the Bar-On Emotional Quotient Inventory, between gifted students and talented students in Bahrain in the direction of gifted students. There were differences between the gifted and the talented students in intrapersonal, adaptability, general mood subtest, and total emotional intelligence scores. Finally, gifted males had higher total emotional intelligence scores than gifted females; talented females had higher interpersonal scores than talented males.